Analysis and design of isolated flyback voltage‐multiplier converter for low‐voltage input and high‐voltage output applications. Issue 6 (1st July 2013) - Zhiguo, Zhang; Lin, Zhou
Abstract : An isolated flyback voltage‐multiplier (VM) converter is presented in this study in light of the basic line frequency voltage‐multiplying rectifier. The proposed circuit with a high conversion ratio operates in discontinuous conduction mode and combines the merits of the VM with flyback converters. It is very suitable to be used in low‐voltage input and high‐voltage output applications where compact size and a high conversion ratio are needed. The operations and prominent characteristics of the circuit are described, and the dynamic and steady‐state transfer function of the output‐voltage/input‐voltage is also derived. A laboratory prototype has been built based on the analysis. The validity of analysis for this circuit is verified by experimental results.